THE ROLE OF THE SOVIET PROPAGANDA FILM AND AN OVERVIEW OF CINEMAS IN THE STALIN'S ERA - Apele, Diana (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2016)
Scientists have discovered that architecture is a reflection of social, political, economic and many other processes occurring in the country, and it changes along with the society, reflecting its social structure within the space and time. In the research the role of cinema in Soviet propaganda is described, the architecture of Stalin era, cinema buildings in Latvia is reviewed and analysed and a film repertory during the existence of the cinema „Zvaigzne” in Rezekne is evaluated. The methods used in the research are based on the study of scientific and journalistic literature materials, which reveal the testimonies of the relevant period in architecture and show the importance of cinema in Soviet propaganda. The aim of the research: to explore and analyze the role of Soviet propaganda, to provide the analysis of architecture of Stalin era cinema buildings and to evaluate a film repertory during the existence of the cinema „Zvaigzne” in Rezekne.